Polyaniline-coupled multifunctional 2D metal oxide/hydroxide graphene nanohybrids - Li, Shuang; Wu, Dongqing; Cheng, Chong; Wang, Jinzuan; Zhang, Fan; Su, Yuezeng; Feng, Xinliang (Angewandte Chemie International Edition, 2013)
Particles and sheets: Polyaniline is used as a linker to couple metal oxides and hydroxides to graphene sheets. Hydrothermal treatment converts these coupled hybrids into nitrogen-doped 2D carbon nanosheets integrated with size-controlled metal nanoparticles. This structure gives these 2D nanohybrids promising electrochemical behavior in supercapacitors and oxygen-reduction reactions. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: graphene; nanoparticles; oxygen-reduction reaction; polyaniline; supercapacitors